2022
DOI: 10.3390/pr10010153
|View full text |Cite
|
Sign up to set email alerts
|

Solar Desalination Driven by Organic Rankine Cycles (Orc) and Supercritical CO2 Power Cycles: An Update

Abstract: In the field of desalination powered by renewable energies, the use of solar power cycles exhibits some favorable characteristics, such as the possibility of implementing thermal energy storage systems or a multi-generation scheme (e.g., electricity, water, cooling, hydrogen). This article presents a review of the latest design proposals in which two power cycles of great potential are considered: the organic Rankine cycle and the supercritical CO2 power cycle, the latter of growing interest in recent years. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…• Four desalination technologies based on phase-change: i) Membrane Distillation (MD), ii) Multi-Effect Distillation (MED), iii) MED with Thermal Vapour Compression (MED-TVC) and iv) Humidification-DeHumidification (HDH) with values of Performance Ratios (PR) taken from recent bibliography on the topic [18,19].…”
Section: Scope Of Work and Objectivesmentioning
confidence: 99%
“…• Four desalination technologies based on phase-change: i) Membrane Distillation (MD), ii) Multi-Effect Distillation (MED), iii) MED with Thermal Vapour Compression (MED-TVC) and iv) Humidification-DeHumidification (HDH) with values of Performance Ratios (PR) taken from recent bibliography on the topic [18,19].…”
Section: Scope Of Work and Objectivesmentioning
confidence: 99%
“…Delgado-Torres and Gacia-Rodrigues [14] reviewed the latest designs in solar desalination driven by organic Rankine cycles (ORC) and supercritical CO2 power cycles as power conversion units. The latter utilizes high and low temperature fluids to recover heat in a process to increase cycle efficiency.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…The chief goal of the paper by Delgado-Torres and Gacia-Rodrigues [14] was the review of the literature and then to give design suggestions. The authors reported that in the mediumtemperature range, there were many studies in which the heat rejected by the cycle was employed to drive processes in thermal desalination as well as absorption cooling.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…Several solar power plants supply feed water or steam to the electrolyzer, which is then returned as liquid water to the Rankine cycle for evaporation [89]. The hydrogen produced by the SOEC units is compressed and stored using a single system shared by all four electrolysis units [90].…”
Section: System Explanationmentioning
confidence: 99%